Sistem Tutorial Berbasis Kecerdasan Buatan Pada Proses Pengambilan Keputusan Perawatan dan Perbaikan Gitar - Agusta Rakhmat Taufani; Harits Ar Ar Rosyid (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Guitar is a popular musical instrument in the world and is a metronome for every use in various music events and its correlation. As a metronome, the guitar must be well standardized on the quality of each part so that sound that comes in line with the user's expectations in this case is the guitarist. Damage to the guitar is something normal because of its intense use so it needs proper handling in the repair process. The easiest thing is to bring a broken guitar to the experts, but when there are not many guitar service experts or a long enough distance to reach it, then guitar repairs need to be done immediately. Therefore, it is necessary to develop a system that can act as a tutor in the maintenance and repair of guitars by utilizing artificial intelligence embedded in the system. With the help of artificial intelligence, it is expected that the system can assist in the decision making of guitar technicians in the process of making guitar repair decisions based on the symptoms that occur. Decision making used uses the certainty factor method based on certainty factors. After going through the equivalence partitioning testing process, in general this system produces a total percentage of 100% on the success of the item test by experts in the testing process of the 25 items tested. Thus the application meets the requirements for making the program, which is readable and valid.